2010
DOI: 10.1111/j.1755-3768.2008.01475.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclo‐oxygenase‐2 expression in photon‐radiated and non‐radiated uveal melanomas

Abstract: ABSTRACT.Purpose: To determine and compare cyclo-oxygenase-2 (COX-2) expression in photon-radiated and non-radiated malignant uveal melanomas and to analyse the correlation between COX-2 expression and prognosis. Methods: Immunohistochemical staining for COX-2 was performed on 21 uveal melanomas that were endoresected after prior stereotactic radiotherapy with photons and on 22 tumours that were treated by endoresection without prior radiotherapy. COX-2 staining was further analysed in respect to cell type, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…SRT was performed ( n = 23 of the 54 patients, 43%) with photons generated by a 6-megavolt linear accelerator. 8 , 21 23 Single-dose irradiation (sdSRT) was initially performed using retrobulbar anesthesia to immobilize the eye, which was later substituted by a functional eye immobilization device for active fixation by the patient. 23 Similarly, fractionated irradiation was performed using a modified mask that enabled the controlled fixation of a light point.…”
Section: Methodsmentioning
confidence: 99%
“…SRT was performed ( n = 23 of the 54 patients, 43%) with photons generated by a 6-megavolt linear accelerator. 8 , 21 23 Single-dose irradiation (sdSRT) was initially performed using retrobulbar anesthesia to immobilize the eye, which was later substituted by a functional eye immobilization device for active fixation by the patient. 23 Similarly, fractionated irradiation was performed using a modified mask that enabled the controlled fixation of a light point.…”
Section: Methodsmentioning
confidence: 99%
“…The COX-2 staining was shown only in 23/40 (57.5%), 52 2/15 (13.3%) 54 or 50/90 (55.6%). 55 Figueiredo et al 52 demonstrated a correlation of the COX-2 expression with the presence of epithelioid melanoma cells assessed according to Callender classification, which indicates higher cancer invasiveness, whereas no such relationships were found by Mougiakakos et al 55 The differences in evaluation of radiotherapy significance for changes in COX-2 levels in eye melanoma cells in papers 52,54,56 may be because of the effect of radiation on many processes, selection of cases for studies, but it is also likely that the choice of anti-COX-2 antibodies was important.…”
Section: Antibodiesmentioning
confidence: 99%
“…In studies of the COX‐2 expression in human eye melanomas, antibodies specific for fragments located at the C‐terminus of this protein were used . COX‐2 was detectable in almost all cases examined: 29/32 (90.6%), 42/42 (100%), and 17/18 (94.4%) . More divergent results were obtained using antibodies described as Ab2 in paper .…”
Section: Possible Causes Of Different Cox‐2 Immunohistochemical Detecmentioning
confidence: 99%
“…C-NFκB proteins (canonical nuclear factor-κB proteins (p65 and p50)), coordinate innate immunity and inflammation processes, particularly important in neoplastic transformation [32]. Other proteins associated with the presence of metastasis are COX-2 (Cyclooxygenase-2), an enzyme which catalyzes the prostanoid synthesis reaction [34], and p53, a cell-cycle regulatory protein [39]. PCNA (proliferating cell nuclear antigen, ATLD2), the DNA polymerase auxiliary protein involved in the control of DNA replication, is also associated with the presence of metastases [61].…”
Section: Metastasismentioning
confidence: 99%
“…COX-2 (Cyclooxygenase-2) [34] Enzyme, which catalyze the prostanoid synthesis reaction. 43 High expression correlates with presence of metastasis.…”
mentioning
confidence: 99%